The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.31018/jans.v9i2.1275
|View full text |Cite
|
Sign up to set email alerts
|

First report of tar spot of Toona (Toona ciliata) in India

Abstract: Abstract:A new foliar disease of toona tree has been reported during continuous surveys conducted at Solan district of Himachal Pradesh during August, 2015 to December, 2015. On the basis of morphological characteristics of the fungus, the fungus was identified as Rhytisma acerinum, which produces symptoms on upper surface of the leaves as numerous small, superficial and blackish lesion which later gives the similar appearance as given by tar. Tar spot of the toona tree produces the ascomata whose size ranges … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
(4 reference statements)
1
1
0
Order By: Relevance
“…We also observed that the germination and viability percentage of both Bauhinia species were recorded higher in polythene bags under room temperature and lower viability was found in cotton bags. The results of our study are at par with that reported for Toona ciliata M. Roem (Meliaceae) [38]. The seeds stored in cotton bags resulted in the loss of seed viability due to the loss of seed moisture during storage, which further affected the longevity of the seeds.…”
Section: Discussionsupporting
confidence: 79%
“…We also observed that the germination and viability percentage of both Bauhinia species were recorded higher in polythene bags under room temperature and lower viability was found in cotton bags. The results of our study are at par with that reported for Toona ciliata M. Roem (Meliaceae) [38]. The seeds stored in cotton bags resulted in the loss of seed viability due to the loss of seed moisture during storage, which further affected the longevity of the seeds.…”
Section: Discussionsupporting
confidence: 79%
“…(Jain et al, 2019). Nigrosora sphaerica that causes leaf spot on Celtis australis (Gautam, 2014) and Rhytisma acerinum that causes tar spot on Toona ciliata (Chandel & Kumar 2017) are some of the pathogenic fungi recorded for the study tree species. Fungal pathogens play crucial roles in producing diseases.…”
mentioning
confidence: 99%